Expanding the value of CLIL: Perspectives from primary to higher education - Jermaine S. McDougald; Claudia Patricia Alvarez Ayure (Universidad de La Sabana, 2021)
The world continues to evolve, where globalization has been the driving factor behind changes in society, thereby creating challenges that could be seen as opportunities in education. Areas such as collaboration, teamwork along with intercultural awareness and communication are just a few of the areas that are being addressed in the educational arena amongst practitioners. Approaches such as Content and Language Integrated Learning (CLIL), Content Based Instruction (CBI) and English as a Medium of Instruction (EMI) have proven to be viable options for bi/multilingual educational environments across the globe. This editorial discusses research from four continents - the Americas, Asia, Europe, and the Middle East (The United States of America, Taiwan, Iran, Mexico, Turkey, Colombia, Puerto Rico, and Italy) - reporting on the diversity in integrating content and language in bi/multilingual teaching environments. Key issues such as children's literature and CLIL, reading comprehension in English as a Foreign Language (EFL), language objectives in lesson plans and assessment in content-based instruction. Furthermore, EMI and the internationalization of higher education, teachers', and students' beliefs on the use of Spanish in an advanced English classroom and the implementation of CLIL in the field of pharmacology will also be discussed, where insights into how content and language are integrated at the different educational levels.